2010
DOI: 10.1002/jcaf.20609
|View full text |Cite
|
Sign up to set email alerts
|

XBRL filings: What have we learned?

Abstract: In January 2009, the Securities and Exchange Commission (SEC) mandated the use of eXtensible Business Reporting Language (XBRL) financial statement reports. The current filing process with the SEC will undergo a major change under XBRL, but the new rules are taking effect over a three‐year phase‐in period. What lessons have we learned from the first wave of XBRL filers with the SEC? And what future planning should Phase 2 and Phase 3 companies undertake? © 2010 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…There are several errors that companies make with respect to the accuracy of XBRLrelated documents (Bartley et al, 2010;Boritz and No, 2008;Debreceny et al, 2010;SEC, 2009b;2010b;Weirich and Harrast, 2010;XBRL US, 2010a …”
Section: Accuracymentioning
confidence: 99%
“…There are several errors that companies make with respect to the accuracy of XBRLrelated documents (Bartley et al, 2010;Boritz and No, 2008;Debreceny et al, 2010;SEC, 2009b;2010b;Weirich and Harrast, 2010;XBRL US, 2010a …”
Section: Accuracymentioning
confidence: 99%
“…According to previous studies (Boritz and No, 2008;Debreceny et al, 2010;Weirich and Harrast, 2010), common errors in XBRL creation are that companies improperly represent the relationship among elements, fail to establish mathematical relationships among elements in a calculation linkbase, and present elements in the wrong location in a presentation linkbase.…”
Section: Compliancementioning
confidence: 99%
“…Studies have shown that several common errors in XBRL creation can occur when companies map business facts in the official financial statements to elements in XBRL taxonomies (Boritz and No, 2008;Debreceny et al, 2010;SEC, 2009b;2010b;Weirich and Harrast, 2010). Some companies have used a less appropriate standard element even though a more appropriate standard element exists.…”
Section: Suitabilitymentioning
confidence: 99%
“…As noted above, research has noted that current XBRL-related documents often contain errors (Bartley et al 2009(Bartley et al , 2011Debreceny et al 2010;Weirich and Harrast 2010;Du et al 2011). As interactive data visualization software that presents financial statement values becomes readily available, investors will be more likely to rely on XBRL-related data.…”
Section: What Are the Potential Benefits And Shortcomings Of Implemenmentioning
confidence: 99%
“…Although the mandate explicitly states that public accountants are not required to provide assurance on these XBRL-related documents, early research (i.e., Bartley et al 2009Bartley et al , 2011Debreceny et al 2010;Weirich and Harrast 2010;Du et al 2011) finds that several documents contain errors. Further, new interactive data visualization software allows for the presentation of individual values from the financial statements (Dilla et al 2010;Janvrin et al 2011).…”
Section: Responses To Specific Questions In the Releasementioning
confidence: 99%